Analisis Akurasi Perhitungan Nilai Ejeksi Fraksi Cardiac Magnetic Resonance untuk Meningkatkan Mutu Layanan Kesehatan di Ruang Radiologi - Pelawi, Awan; Harahap, Veryyon; Purba, Yeni Trisna; Zalukhu, Nomelda; Sijabat, Auhon Berkat (3031-8572, 2023)
Ejection Fraction (EF) is a parameter for assessing the heart's ability to pump blood throughout the body. Currently, ultrasound is frequently used to detect EF values, but it has limitations such as poor acoustic window and operator dependency. Cardiac Magnetic Resonance (CMR) examination has advantages in providing accurate EF values with two measurement methods: Short Axis and Long Axis view. This study aims to determine the accuracy of left ventricular ejection fraction values in CMR examination using short axis and long axis view methods compared to echocardiography. Method: descriptive quantitative research design on EF calculation conducted at radiology installation in Jakarta hospital from July-October 2022 with 33 patient samples. Data were obtained through observation and measurement using CVI 42 software on 1.5T GE Signa Voyager MRI device. Results: The average EF percentage on LVEF-EC measurement method was 41%, LVEF-SA 40%, and LVEF-LA 43%. The accuracy showed EC-SA average difference of 0.939 with 3% percentage and EC-LA average difference of 1.812 with 5% percentage. Conclusion: Short axis method is more accurate compared to long axis, thus can be used as standard procedure for CMR examination to provide quality diagnostic services.